Lokmanya Bal Gangadhar Tilak's Śrīmad Bhagavadgītā Rahasya or Karma Yoga-Śāstra - Tilak, Bal Gangadhar, (Brill | Manohar Publishers & Distributors, 2024)
After Jñānēśvarī, ŚrīmadBhagavadgītāRahasya is the Marathi translation and commentary on Gita written by Tilak, while he was serving his prison term at Mandalay, Burma. The text was completed in Mandalay Jail from 1908 to 1914, and was published in 1915 when he returned to Poona. The English translation was done by B.S. Sukthankar in 1934. In his commentary, he gave high emphasis to nishkāmakarmayoga (selfless action) over karma sanyāsa (renouncing actions). Also, he gave importance to the Mimā]nsa rule of interpretation, which is part of the tradition of contemplation, which is followed to discover the meanings in the Vedic texts. The first part contains the philosophical exposition and the second part contains the Gita text, its translation, and commentary. He interprets the message of Gita by the subservience of all yogas to karma yoga (yoga of action) rather than jñāna yoga (yoga of knowledge) or bhakti yoga (yoga of devotion).